Assessing the effects of different management activities on the conservation of endangered Indo-Pacific humpback dolphin - Lu, Yi; Zhuo, Haojie; Xu, Xinrong; Chen, Bingyao; Yang, Guang (Frontiers in Marine Science, 2023)
Predictions of population viability can provide valid information for guiding the management and conservation of species. However, such studies are rarely conducted on cetaceans due to limited basic data. In this study, a detailed assessment of the population dynamics of Indo-Pacific humpback dolphins (Sousa chinensis) in Xiamen Bay, China was carried out using a Vortex model that was based on model parameters that were derived from monitoring data and published sources. Then, sensitivity analyses were conducted to test the relative importance of the uncertainty of the model parameters. Moreover, potential management models were evaluated to determine their effectiveness in assisting with species recovery. The baseline model projected a decline in the population abundance with a growth rate (r) of -0.031, and the probability of extinction was 58.7% over the next 100 years. The sensitivity analyses revealed that juvenile mortality and fertility were the most pivotal factors for the viability of this population. All the conservation measures, including habitat improvement, catastrophe control, and individual supplementation, contributed to population increases when compared with the baseline model. In particular, decreasing calf and juvenile mortality through habitat improvement, at high levels, was the only way to generate positive growth rates. The findings suggest that these practical management activities can reduce the risk of extinction for this species.